Advances in Quantum Communication and Information - Bulnes, Francisco; Stavrou, Vasilios N.; Morozov, Oleg; Bourdine, Anton V. (IntechOpen, 2020)
Research in quantum communication requires knowledge of the information theory and teleportation of information in any physical form using the quantum field as media of all different processes and aspects on the managing of their information, their boson processing and their technologies. Likewise, one of the most important principles in researching is the quantum intertwining to define the management of communication of the quantum type. Other aspects related to the design of technologies to the quantum communication base and their development on transceptor models of Bose-Einstein observation nature to form a quantum laser wave of atoms. This quantum wave is a wave-links chain that defines and determines the quantum communication. Quantum computing models are very useful to establish the programming order required in the quantum communication processes. The present book is a compilation of the chapters that cover several of these themes and in other cases, put the field theories to test regarding what is quantum communication and its technologies.